Evaluation of muscle strength in young and top-level soccer players - Sannicandro, I. (Medicina dello Sport, 2011)
Aim. The study to assess the strength levels in soccer highlight differences between the junior categories and the top level in Italy. To check also the progress of the strength levels in young players to understand if the player of "Primavera" class has the strength ability in order to participate and compete in the greatest national championship.